Exochelin production in Mycobacterium neoaurum. - Chan, K. (MDPI, 2009)
Mycobacterium neoaurum is a soil saprophyte and obligate aerobic bacterium. This group of mycobacterium is relatively fast-growing. They form colonies on nutrient agar at 37 masculineC within 3 - 4 days. In natural soil habitats, bioavailability of iron is limited. To facilitate iron uptake, most mycobacteria produce siderophores. One example is exochelin, which is extracellular and water-soluble. In this report, the production of exochelin in M. neoaurum was induced in iron-deficiency, but repressed under ironsufficiency growth conditions. It is however not induced under zinc-deficiency growth conditions. The growth of this mycobacterium was correlated with exochelin secretion under iron-deficiency culture conditions. When M. neoaurum was grown in defined medium containing 0.04 microg Fe(III)/mL (final concentration), the production of exochelin reached a maximum and the corresponding cell growth was comparable to that under iron-sufficiency conditions. In this study, exochelin was purified from spent supernatant of M. neoaurum by semi-preparative chromatography. When saturated ferric chloride solution was added into the purified exochelin, a ferri-exochelin complex was formed. It is proposed that iron uptake in M. neoaurum is exochelin-mediated.